2020
DOI: 10.3390/ma13215000
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, Thermal, and Moisture Buffering Properties of Novel Insulating Hemp-Lime Composite Building Materials

Abstract: Hempcrete is a sustainable biocomposite that can reduce buildings’ embodied energy while improving energy performance and indoor environmental quality. This research aims to develop novel insulating hemp-lime composites using innovative binder mixes made of recycled and low-embodied energy pozzolans. The characterization of composites’ mechanical and hygrothermal properties includes measuring compressive strength, splitting tensile strength, thermal conductivity, specific heat capacity, and moisture buffer cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Other studies have also confirmed that density, which is a function of compaction, as a crucial production factor affecting the performance of the lime-hemp concrete (Barna-Hunek et al 2015;Abdellatef et al 2020).…”
Section: Fig 1 Schematic Diagram Illustrating the Compaction Casting Techniquementioning
confidence: 84%
“…Other studies have also confirmed that density, which is a function of compaction, as a crucial production factor affecting the performance of the lime-hemp concrete (Barna-Hunek et al 2015;Abdellatef et al 2020).…”
Section: Fig 1 Schematic Diagram Illustrating the Compaction Casting Techniquementioning
confidence: 84%
“…Another studied aspect is the adoption of recycled and locally sourced materials for improving the properties of hemp-lime composites. For instance, Abdellatef et al [ 51 ] experimented with the use of recycled crushed brick as a pozzolan to create more environmentally-friendly hemp-lime composites. Their results indicated that mixes with a 1:1 binder to hemp ratio and 300–400 kg/m 3 density had hygrothermal and mechanical properties suitable for insulating infill wall applications.…”
Section: State-of-artmentioning
confidence: 99%
“…Assume UN represents the apparent solar time, then the solar time angle θ can be calculated according to Eq. (15): ( ) 15 12…”
Section: Construction Of the Hygrothermal Transfer Modelmentioning
confidence: 99%
“…Johra et al [14] constructed an indoor hygrothermal environment model which is composed of an indoor hygrothermal balance equation and a coupled faç ade hygrothermal transfer model, they tested the change law of indoor hygrothermal environment under different weather conditions and applied actual cases to analyze the impact of different building envelop structures on the cooling load of air conditioners, the heating load of heaters, and the indoor hygrothermal environment; then they proposed a set of indoor hygrothermal environment regulation methods that suit the load characteristics of zero energy consumption buildings. The coupled hygrothermal transfer of external facade materials have a great impact on the energy consumption of air conditioners and the indoor hygrothermal environment [15][16][17][18]. Mukai et al [19] researched the theories of coupled hygrothermal transfer in buildings, they built an experimental platform to measure the temperature, relative humidity, and indoor and outdoor temperatures and compared the measured results with the simulation values; at the same time, they also compared the indoor temperature, relative humidity, heat flow, and humidity flow of the inner layer materials and insulation materials of buildings under natural conditions, and used the WUFI-Plus software to simulate energy consumption with humidity transfer time taken into consideration.…”
Section: Introductionmentioning
confidence: 99%